The Experiences of Mothers with Intrauterine Fetal Death/Demise (IUFD) in Indonesia - Sinaga, Alma Dormian; Purwarini, Justina; Anggraeni, Lina Dewi (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Intrauterine Fetal Death/Demise (IUFD) is a traumatic event for mothers. Mothers with IUFD have the risk of experiencing depression, anxiety, sadness, and sorrow in their lives. Research focusing on how mothers deal with such a traumatic experience is therefore necessary.Purpose: This study aimed to explore the experiences of mothers with Intrauterine Fetal Death/Demise (IUFD) in Indonesia.Methods: A descriptive qualitative study with a phenomenological approach was carried out to seven informants who were recruited using a purposive sampling technique. Data were collected through in-depth interviews and analyzed using Colaizzi's method.Result: The results showed four major themes, including the mothers’ response to a loss such as painful and traumatic experience; moral support received by mother; negative behavior from others such as stigma and lack of support; and physical and psychological changes that interfere with the role as wife and mother.Conclusion: The history of IUFD is a very traumatic experience and has a quite high emotional burden for mothers. Hence, it is necessary to integrate support and therapeutic communication into practice.